In the foothill zone—Sabanejewia balcanica (Karaman 1922), in the lowland zone—Sabanejewia bulgarica (Drensky, 1928): Myth or reality?. Issue 14 (3rd July 2020) - Križek, Peter; Mendel, Jan; Fedorčák, Jakub; Koščo, Ján
Abstract: The status of golden loaches (genus Sabanejewia ) in the region of Central Europe and Balkans is still ambiguous. The greatest controversy is caused by species Sabanejewia balcanica and S. bulgarica . Both species are characterized by a wide spectrum of morphological variability and overlapping of distinguishing features, which then lead to difficulties in their determination. Previous phylogenetic studies aimed on the resolving of their taxonomic status did not include samples from their type localities and so led to a lack of their true distribution in this region. Therefore, the main aim of this study was to identify taxonomic status of golden loaches populations in the region of the middle Danube basin and adjacent areas on the model territory of Slovakia. For this purpose, we used novelty approach (morphological, molecular, and microhabitat) and we also included the missing samples from the type localities of both species. Based on mtDNA all the Slovakian samples reflected haplotype richness revealed on the type locality of S. bulgarica, although the genetic distances from other representatives of the genus Sabanejewia occurring are not significant. Within the morphology, we have revealed a great measure of variability in studied populations, which is largely caused by different habitat conditions and thus representing a phenotypic plasticity of these fish. Abstract : The work deals with the ecologic and molecular status of Vladykov's Golden loach in selected European river basins. Our study is the first to report the remarkable results achieved using a new molecular, morphological, and ecological approach, which provides the basis for further studies.